Geometric maximum power point tracking and sliding mode control of a bidirectional grid connected single phase two‐stage photovoltaic system with DC loads. Issue 9 (23rd June 2016) - Shen, Liqun; Lu, Dylan Dah‐Chuan; Wang, Yanmin
Abstract : This study proposes a new geometric maximum power point tracking (MPPT) method for photovoltaic (PV) power system. The reference point can be calculated and updated in real time directly with the proposed method. The reference point will converge to the real maximum power point (MPP) when approaching MPP. This can improve the MPPT speed comparing with the commonly used step‐by‐step optimisation. The MPPT method is applied to a DC bus coupled grid‐connected PV system with the presence of DC loads, and an adaptive sliding mode controller is designed for the whole system. The proposed control scheme performs the MPPT and the power allocation between the PV array and the grid adaptively. With adaptive method, the converter can control the power flow bi‐directionally to balance the power supply and consumption under a unity power factor. Simulation and experimental results are reported to confirm the proposed approach.